Phase diagram of mixed monolayers of stearic acid and dimyristoylphosphatidylcholine. Effect of the acid ionization - Vega Mercado, Franco (2011)
The aim of this work is to study the phase diagram of mixed monolayers composed of dimyristoylphosphatidylcholine (DMPC) and stearic acid (SA) at different ionic strength and bulk pH of the aqueous subphase. In this way, the effect of ionization of SA on the interaction and thus on phase separation with the DMPC matrix can be analyzed. To this purpose, we first determined the ionization state of pure SA monolayers as a function of the bulk subphase pH. The SA monolayers are nearly fully ionized at pH 10 and essentially neutral at pH 4 and the mixture of DMPC and SA was studied at those two pHs. We found that the DMPC-enriched phase admits more SA if the SA monolayer is in a liquid-expanded state, which is highly related to the acid ionization state, and thus to the bulk pH and ionic strength. At pH 4 the molecules hardly mix while at pH 10 the mixed monolayer with DMPC can admit between 30 and 100% of SA (depending on the lateral pressure) before phase separation is established. The addition of calcium ions to the subphase has a condensing effect on SA monolayers at all pHs and the solubility of SA in the DMPC matrix does not depend on the bulk pH in these conditions. The observed phase diagrams are independent on the manner in which the state of the mixed film is reached and may thus be considered states of apparent equilibrium. © 2011 Elsevier Ireland Ltd. All rights reserved.